Virtual teams formation: Remote team building and leadership - L. V. Kozhevnikova; I. E. Starovoytova (Вестник университета, 2022)
The article examines the problem of increasing the efficiency of virtual teams, a specific form of labor organisation in the digital economy. The relevance of remote team building of virtual teams is revealed. The essence of the remote team and team building is investigated. Based on the study of the results of empirical sociological research, the advantages and disadvantages of virtual teams are determined. The problem of remote team building technologies, team building methods at all stages of virtual team formation is raised. The main directions of the team leadership transformation are revealed. The problems faced by the leadership of virtual teams at differents stages of their formation, group dynamics are shown remote team-building tools for their resolution are suggested. The results of the article can be used in further research on the problems of organising teamwork in the digital economy, in developing proposals and recommendations for specialists in the field of personnel management for use in practice.